The Role of Italian Occupation of Ethiopia On the Egyptian- Italian Relations 1935 - عبد المجيد كامل عبد اللطيف زينب خالد حسين (College of Education for Women, 2019)
When the Italian fascist party leaded & access to the top of regime, it took Benito Mussolini as a post of Italian prime minister on 1922, that lead to rise the voices which need to find colonies of Italy, like other colonial countries, especially that of its colonies in Libya, Eritrea and Somalia were not achieved its ambitions, was to be the occupation of Ethiopia to revive her dreams to exert control over the Red sea and the Mediterranean and the establishment of a vast empire satisfy colonial ambitions. the Italian invasion of Ethiopia gained particularly important, what led to the disruption of the balance of political forces is not at the level of local powers in the region, but at the level of the extended diagonals on the west coast of the red sea and horn of Africa. Egypt had a clear position from the occupation of what connects Ethiopia common interests, particularly the source of the river Nile. The research which divided in to the introduction, two sections, and conclusion, taking the first section of the Egyptian official position of the Italian occupation of Ethiopia, and economic sanctions against Italy, while the second topic addressed the Egyptian popular position of the Italian occupation of Ethiopia. The research depend on a variety of sources documents come in the forefront, including documents unpublished in the library and archives in Baghdad, the British and the documentation is not published, as well as published documents, which was the documentary books, as research on Arab and foreign sources, newspapers and magazines adopted.The Egyptian-Italian relations took a gradual decline in the wake of the Italian occupation of Ethiopia in 1935, and was the Egyptian official position is identical with the British position, at the beginning of it, but it evolved over the public pressure to stand opposed to the occupation, especially after realizing Egyptian politicians that control of Italy to Ethiopia means of control Lake Tana, source of the Nile and then it will be the lifeblood of Egypt is vital, however, Italy, not to mention the control of Italy to Libya, and that means the occurrence of Egypt between pliers Italy, so what that floated the idea of economic sanctions against Italy until the Egyptian government announced its acceptance to apply those sanctions, despite the lack of participation membership in the nations league, but they saw the U.N. resolution only door that it can stand against the Italian expansion. He was to participate in the Egyptian penal significant role in disturbing the relations with the Italians, who claimed that they understands the Egypt's position on the grounds that he came according to what you want Britain. Was a popular position Egyptian prominent role in the Italian war Ethiopian, as opposed strongly the Italian occupation of the Egyptians felt the seriousness of the occupation on their lives and their future, and they keep their best to share with Ethiopians to repel the Italian aggression and demonstrated dramatically by sending material and humanitarian aid to Ethiopia was the Egyptian medical missions a big role to help the war-wounded from the Ethiopians, as was the Egyptian parties and the press a large role in stirring public opinion against the Italian occupation of Ethiopia.